2015
DOI: 10.1155/2015/270501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cultivation Time and Medium Condition in Production of Bacterial Cellulose Nanofiber for Urease Immobilization

Abstract: A new nanoporous biomatrix originated from bacterial resources has been chosen for urease immobilization. Urease has been immobilized on synthesized bacterial cellulose nanofiber since this enzyme has a key role in nitrogen metabolism.Gluconacetobacter xylinumATCC 10245 has been cultivated for synthesis of a nanofiber with the diameter of 30–70 nm. Different cultivation processes in the aspect of time and cultivation medium conditions were chosen to study the performance of immobilized enzyme on four types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is also seen that the CNF looks like whiskers. The results indicated that the CNF obtained has a nanoscale [25]. Another study reported that CNF isolated from a pineapple leaf using steam explosion had an interconnected web-like structure with a width between 5 nm and 60 nm [26].…”
Section: Morphological Properties Of Cellulose Nanofibre and Ligninmentioning
confidence: 86%
“…It is also seen that the CNF looks like whiskers. The results indicated that the CNF obtained has a nanoscale [25]. Another study reported that CNF isolated from a pineapple leaf using steam explosion had an interconnected web-like structure with a width between 5 nm and 60 nm [26].…”
Section: Morphological Properties Of Cellulose Nanofibre and Ligninmentioning
confidence: 86%
“…When BC is incorporated in various polymeric matrices, they impart new set of properties to the composites, thus allowing such innovative materials to be applied in various areas [25,26], including pharmaceutics and biomedicine [22]. It has previously been shown that BC can also be used to immobilize various enzymes [27,28,29,30]. However, studies on the effect of BC production and cultivation conditions on the properties of immobilized enzymes are rather limited [27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, glucoamylases for hydrolysis of starch to glucose in bioethanol production [8]. Also, work is underway to create composites based on BC/Ch with immobilized ureases, which are used to detoxify blood in artificial kidneys, remove urea from drinks and food products, and reduce the content of urea during wastewater treatment [9]. Adsorption immobilization converts the enzyme from among homogeneous For the sorption immobilization of metabolites contained in B. subtilis P-2 CFS, pieces BC film were introduced into this cell-free extract and incubated at room temperature (25 ° C) under dynamic conditions (80 rpm) for 5 minutes.…”
Section: Resultsmentioning
confidence: 99%